Openness to Change Scale in Higher Education: Adaptation and Validity of the Indonesia Version - Neka Erlyani; Rahkman Ardi; Fendy Suhariadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
As change is unavoidable, there is a need for reform in higher education systems across the world. One’s openness to change is one of the many elements contributing to an effective change. There is a need for a capable instrument to assess openness to change within the higher education sector. This study investigates the scale developed by Miller for use in Indonesia. The research matches its findings with the pioneering work, offering insight into the CFA analyses performed. The findings revealed results on scale adaptation, substantiating its strong validity, internal consistency, and reliability. The scale contributes considerably to the academic discourse around transformational dynamics within higher education institutions by providing a tangible method for assessing their openness to change.